CDKN2A-independent role of BMI1 in promoting growth and survival of Ph+ acute lymphoblastic leukemia - Mariani, Samanta Antonella (Leukemia, 2016)
BMI1 is a key component of the PRC1 complex (polycomb repressive complex-1) required for maintenance of normal and cancer stem cells. Its aberrant expression is detected in chronic myeloid leukemia and Ph+ acute lymphoblastic leukemia (ALL), but no data exist on BMI1 requirement in ALL cells. We show here that BMI1 expression is important for proliferation and survival of Ph+ ALL cells and for leukemogenesis of Ph+ cells in vivo. Levels of BIM, interferon-α (IFNα)-regulated genes, and E2F7 were upregulated in BMI1-silenced cells, suggesting that repressing their expression is important for BMI1 biological effects. Consistent with this hypothesis, we found that: i) downregulation of BIM or E2F7 abrogated apoptosis or rescued, in part, the reduced proliferation and colony formation of BMI1 silenced BV173 cells; ii) BIM/E2F7-double silencing further enhanced colony formation and in vivo leukemogenesis of BMI1-silenced cells; iii) overexpression of BIM and E2F7 mimicked the effect of BMI1 silencing in BV173 and SUP-B15 cells and iv) treatment with IFNα suppressed proliferation and colony formation of Ph+ ALL cells. These studies indicate that the growth-promoting effects of BMI1 in Ph+ ALL cells depend on suppression of multiple pathways and support the use of IFNα in the therapy of Ph+ ALL.